MODERN METHODS OF EXAMINATION FOR SUSPECTED BREAST CANCER (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
A high degree of mammary gland diseases is considered to be one of the main factors that significantly affect the health of women. The number of new cases of breast cancer detected annually in different countries of the world today has exceeded 1 million and is 10% of all malignant tumors of various localizations.[8]. Despite the success in the cure and the increase in the ability to diagnose this pathology, the mortality rate from breast cancer remains significant. This is due, in general, to the late diagnosis of this pathology in conjunction with the untimely call of patients, and in addition, the lack of highly sensitive methods for determining the early stages of breast cancer, insufficiently clear diagnosis of metastases in regional lymph nodes [9].